2015
DOI: 10.3389/fpsyg.2015.01874
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Language Across Early Childhood: Family Socioeconomic Status does not Impact Boys and Girls Equally

Abstract: Child sex and family socioeconomic status (SES) have been repeatedly identified as a source of inter-individual variation in language development; yet their interactions have rarely been explored. While sex differences are the focus of a renewed interest concerning emerging language skills, data remain scarce and are not consistent across preschool years. The questions of whether family SES impacts boys and girls equally, as well as of the consistency of these differences throughout early childhood, remain ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 64 publications
7
46
1
6
Order By: Relevance
“…Our results are, however, in line with previous findings: If there is a (direct or indirect) gender influence on early expressive vocabulary at all, it is small. They are also consistent with recent findings reporting gender differences in language acquisition in low but not in high SES children (Barbu et al, 2015). The expected performance overlap between genders is large, making the relevance of such presumed differences for everyday communication and early childhood education at least questionable.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are, however, in line with previous findings: If there is a (direct or indirect) gender influence on early expressive vocabulary at all, it is small. They are also consistent with recent findings reporting gender differences in language acquisition in low but not in high SES children (Barbu et al, 2015). The expected performance overlap between genders is large, making the relevance of such presumed differences for everyday communication and early childhood education at least questionable.…”
Section: Discussionsupporting
confidence: 93%
“…Due to limitations regarding the size of the subgroups (only seven girls did not attend daycare), this interaction has to be interpreted with caution. Also, we cannot make any conclusive claims about the underlying reasons for these differences, but they could relate to parental communication behavior (Bohman et al, 2009 ; Harris et al, 2010 ; Hart & Risley, 2003 ; Hoff, 2006 ; Rohacek et al, 2010) and complement recent reports on differential effects of environmental variables for boys and girls (Barbu et al., 2015 ; Berglund et al, 2005 ; Vallotton et al, 2012 ; Zambrana et al, 2012). …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Whether gender is a meaningful source of variation in language abilities has remained a matter of debate across the decades (Barbu et al, 2015). Although in general intelligence, there is not a marked gender difference discovered by research (Furnham & Rawles, 1995), studies have found some differences in learning reading and math between the genders: male students than females tend to have better math performance outcomes (Cimpian, Lubienski, Timmer, Makowski, & Miller, 2016); females have slightly better verbal skills than males (Galambos, Berenbaum, & McHale, 2009).…”
Section: Gendermentioning
confidence: 99%
“…Earlier studies suggest that gender is a fundamental factor for variation (Maccoby and Jacklin, 1974;Fenson et al, 1994), whereas more recent ones claim the exact opposite (Hyde, 2005;Wallentin, 2009). In an attempt to resolve the debate, Barbu et al (2015) investigated not only gender differences but also children's socioeconomic status (SES) who acquired a frequent phonological alternation in French between the ages of around 2.5 and 6.5 years. Gender differences were only found for children with low SES, whereas low-SES boys performed worse Apparent optionality in clitic placement in certain syntactic environments has also occasionally been noted for adult CG, culminating in separate (sociolinguistic) empirical investigations in which Pappas (2012Pappas ( , 2014 reports a certain level of variability.…”
Section: Toward Capturing the Socio-syntax Of Development Hypothesismentioning
confidence: 99%